О культурно-хронологической принадлежности памятников малобудковского типа эпохи бронзы - Буйнов, Ю.В. (My University, 1994)
Buynov Yu. V. On Cultural and Chronological Appertainance of the Malobudkovtki Site Type Monuments Dated to the Bronze Age The article deals with the problems of chronology and periodization ot the Bronze Age. monuments of Mali Budki type. The data and things available the author proves procuding from these monuments should be dated from later time — XII and middle XI c. B, C. The new materials confirm the sorting out of Mali Budki stage in Bondarihin culture.